2015
DOI: 10.4238/2015.december.14.9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic influence of NF-κB and EGFR in esophageal cancer

Abstract: ABSTRACT. The goal of this study was to investigate the expression profiles of nuclear factor-kappa B (NF-κB) and epidermal growth factor receptor (EGFR) in esophageal cancer and to determine their association with tumor prognosis. This study included 40 esophageal cancer patients [22 men and 18 women; average age = 62.7 ± 3.9 years; tumor-node-metastasis (TNM) staging: 12 patients with stage I, 13 patients with stage II, and 15 patients with stage III disease]. Tumor tissues and tumor-adjacent tissue specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“… 40 The expression of EGFR was reported to be significantly correlated with clinical stage, tumour invasion and poor prognosis. 27 29 , 41 Similarly, our study indicated that EGFR expression was associated with T stage and poor prognosis. Radiotherapy with EGFR tyrosine kinase inhibitors has been tested in many trials with encouraging results.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“… 40 The expression of EGFR was reported to be significantly correlated with clinical stage, tumour invasion and poor prognosis. 27 29 , 41 Similarly, our study indicated that EGFR expression was associated with T stage and poor prognosis. Radiotherapy with EGFR tyrosine kinase inhibitors has been tested in many trials with encouraging results.…”
Section: Discussionsupporting
confidence: 57%
“…4a ), consistent with the findings of previous research reports. 27 29 When treated with erlotinib, patients with EGFR expression (+2, +3) had a significantly longer OS than patients without EGFR expression (0, +1) (median, 46.5 vs 9.5 months; P = 0.007, Fig. 4b ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that NF-κB is constitutively activated in high-grade squamous intraepithelial lesions and squamous cell carcinomas of human uterine cervix [ 24 ]. Numerous previous studies suggested that NF-κB activation not only contributes to the migration and invasion of cancer cells, but also affects cell survival and gene expressions related to tumor proliferation and metastasis [ 25 - 27 ]. Five subunits of NF-κB have been identified, namely, gp105/p50 (NF-B1), p100/p52 (NF-B2), p65 (RelA), RelB, and c-Rel [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…VEGFR-2 and Nuclear Factor Kappa B(NF-kB)-positive substances are mainly localized in the cytoplasm and are brownyellow granular.Ten visual elds were randomly selected under high magni cation(x400),and the percentage of positive cells was calculated in each eld. The number of positive cells in the whole section was ≥5%, which was judged as positive, and <5%was negative [9]. MVD is judged rst at the low magni cation (x100), to observe the highest blood vessel density in the tumor.…”
Section: Patient Characteristicsmentioning
confidence: 99%